Peran Orang Tua Terhadap Perkembangan Psikososial Anak Usia Dini - Damanik, Syahruddin; Lubis, Hilda Zahra (Universitas Muhammadiyah Sumatera Utara, 2022)
The writing of this article aims to determine the role of parents in the psychosocial development of early childhood. The approach method in this research is library research (library). The results showed that the role of parents in the psychosocial development of early childhood is very important and a mandatory responsibility. Parents as gems and primary educators for a child at home and in their social environment, even though they have been entrusted to school, the teacher is only a link for parents so that their children get better education and guidance. Psychosocial development of children is influenced by the pattern of parenting given by parents to children, in which the parenting pattern will determine the good and bad development of children in the future as the next generation and social beings in their environment. The role of parents in this case is to provide warm, caring and loving family care to the fullest. Thus the child will later grow into an adult human who has good self-quality and is able to develop in a strong and confident social environment.